Exploring Herbal and Natural Product Use as a Preventive Health Strategy During COVID-19: Insights from District Qilla Abdullah, Balochistan - Bibi, Sakina; Bibi, Tahira; Jamil, Nelofer; Channa, Farah Naz; Sajjad, Naheed; Ahmed, Hina Ali; Shaukat, Kanval; Khan, Nazima Yousaf; Masood, Ayeesha (Journal of Neonatal Surgery, 2025)
COVID-19 pandemic significantly impacted global health systems, particularly in rural and resource-limited regions, where communities often rely on traditional medicine for managing infections. In District Qilla Abdullah, Balochistan, Pakistan, local populations turned to indigenous medicinal plants to treat and prevent COVID-19-related symptoms such as fever, cough, sore throat, fatigue, loss of taste, diarrhea and respiratory difficulties. This study aimed to document and analyze the prevalence and cultural importance of herbal remedies used during the pandemic. Ethnobotanical data were gathered through interviews with traditional practitioners and local residents. A total of 80 plant species belonging to 38 botanical families were identified, Lamiaceae family emerged as the most dominant, represented by 12 species. Quantitative indices, including Relative Frequency of Citation (RFC), Use Value (UV), Family Importance Value (FIV), Fidelity Level (FL), and Use Reports (UR), were employed to evaluate the relevance of each plant. Trachyspermum ammi L. recorded the highest RFC (0.05) and FIV (4.5), reflecting its widespread use across the region. Other culturally significant species included Adiantum capillus-veneris, Artemisia vulgaris L., and Zingiber officinale Roscoe, each with an FIV of 4.0. Remarkably, Camellia sinensis L. Kuntze and Terminalia chebula Retz. showed a Fidelity Level of 100%, indicating unanimous agreement among informants regarding their efficacy in symptom management. In terms of usage diversity, Adiantum capillus-veneris had the highest Use Reports (UR = 6), followed by Glycyrrhiza glabra L. with five distinct therapeutic applications. Despite the documented therapeutic value of these species, access was hindered by challenges such as seasonal unavailability and elevated market prices during the pandemic. This study highlights the enduring relevance of traditional medicinal knowledge in rural healthcare systems and underscores the importance of integrating validated ethnobotanical practices into formal healthcare policies, especially in the context of public health emergencies like COVID-19. These findings also provide a foundational dataset for future pharmacological investigations and conservation planning of medicinal plant resources in the region.